THE VOICES OF SUBALTERN IN IN THE NOVELS OF AMISH TRIPATHI’S THE SHIVA TRILOGY - Ms.T.Priya (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
THE VOICES OF SUBALTERN IN IN THE NOVELS OF AMISH TRIPATHI’S THE SHIVA TRILOGY